CD276 as a promising diagnostic and prognostic biomarker for bladder cancer through bioinformatics and clinical research - Zhou, Qi; Xu, Jianhao; Chen, Xuelei; Ouyang, Jun; Mao, Caiping (Frontiers in Oncology, 2024)
ObjectiveTo assess CD276 expression and explore its relationship with the clinicopathological characteristics and prognosis of patients with bladder cancer.MethodsIn total, RNA-sequencing data and clinical profiles of 436 bladder cancer cases from The Cancer Genome Atlas (TCGA) were assessed using the University of California Santa Cruz Xena (UCSC) platform. We compared the CD276 levels in cancerous and adjacent normal tissues and used the R software for statistical association with the clinical stage, grade, and survival (the overall survival, disease-specific survival, and progression-free survival). A single-gene GSEA analysis on TCGA-BLCA data was performed to explore potential pathways through which CD276 might influence bladder cancer. Additionally, CD276 expression was analyzed by comparing data from 9 cancerous tissues and 3 adjacent normal tissues in the GEO dataset GSE7476. Furthermore, we analyzed 133 cancerous bladder and adjacent tissue samples from the Soochow University Hospital, collected between January 1, 2016, and September 30, 2022, to assess the CD276 protein expression using immunohistochemistry. We examined the relationship between tumor CD276 levels and clinical outcomes and prognosis of bladder cancer.ResultsBioinformatic analysis revealed elevated CD276 expression in tumors compared to that in adjacent tissues (p<0.05), correlating with poor survival. GSEA revealed that CD276 was significantly involved in extracellular matrix-related pathways. Immunohistochemistry confirmed CD276 overexpression in tumor tissues, with higher levels linked to advanced pathological grades and worse prognosis.ConclusionCD276 is markedly upregulated in bladder cancer and associated with severe pathological features, advanced disease, potential for metastasis, and diminished survival rates. It may promote bladder cancer development and progression by influencing extracellular matrix-related-related pathways, making it a viable diagnostic and prognostic biomarker for bladder cancer.